2014
DOI: 10.1177/0956797613518350
|View full text |Cite
|
Sign up to set email alerts
|

Positive Thinking About the Future in Newspaper Reports and Presidential Addresses Predicts Economic Downturn

Abstract: Previous research has shown that positive thinking, in the form of fantasies about an idealized future, predicts low effort and poor performance. In the studies reported here, we used computerized content analysis of historical documents to investigate the relation between positive thinking about the future and economic development. During the financial crisis from 2007 to 2009, the more weekly newspaper articles in the economy page of USA Today contained positive thinking about the future, the more the Dow Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
(26 reference statements)
0
18
0
Order By: Relevance
“…Proteus effects have repeatedly been shown to exceed effects of passive viewing (Ahn et al, 2016;Banakou et al, 2013;, with asynchronous avatar movements extinguishing the effect (Banakou et al, 2013;compare Tamborini et al, 2018). Additionally, when taking the subjective IVR experience into account, subjective feelings of body ownership of the avatar were shown to mediate Proteus effects (Ahn et al, 2016;Yoon & Vargas, 2014). It has also been suggested that a threshold of subjective body ownership may have to be exceeded for avatar effects to occur (Ash, 2016).…”
Section: Proteus Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteus effects have repeatedly been shown to exceed effects of passive viewing (Ahn et al, 2016;Banakou et al, 2013;, with asynchronous avatar movements extinguishing the effect (Banakou et al, 2013;compare Tamborini et al, 2018). Additionally, when taking the subjective IVR experience into account, subjective feelings of body ownership of the avatar were shown to mediate Proteus effects (Ahn et al, 2016;Yoon & Vargas, 2014). It has also been suggested that a threshold of subjective body ownership may have to be exceeded for avatar effects to occur (Ash, 2016).…”
Section: Proteus Effectmentioning
confidence: 99%
“…Under desktop conditions, embodiment has been found to act as a moderator in avatar effects (Ash, 2016); postulated mediator effects could so far not be established (Yoon & Vargas, 2014). The effects of embodying an avatar in monitor-based games on later behavior were also shown to exceed effects of passive viewing conditions (Yoon & Vargas, 2014).…”
Section: Reach Of Proteus Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on positive thinking has indicated that positive thoughts and images about the future are associated with a lower likelihood of positive outcomes across a variety of contexts, including achievement-related outcomes (see Oettingen, 2012). For example, Sevincer, Wagner, Kalvelage, and Oettingen (2014) found that positive thoughts about the future in U.S. presidential inaugural addresses predicted economic declines in subsequent presidential tenures. Similarly, students with positive thoughts about an upcoming exam appear to achieve lower course grades than other students (Oettingen & Mayer, 2002).…”
Section: What About the Drawbacks Of Optimism?mentioning
confidence: 99%
“…Indeed, repeated simulation has a similar influence on the perceived plausibility of specific events (see above) and general states of the world (e.g., the more often people imagine a particular candidate winning an election, the more likely they are to think the candidate will be elected) (52). Moreover, positive fantasies about an idealized future in the context of newspaper reports and presidential addresses have been shown to predict negative economic downturns (53). At this point, considerable work remains to be carried out to develop an understanding of the extent to which episodic and semantic predictions about the occurrence of future events and states of the world differ beyond the content on which they operate (e.g., are people who are good at predicting general states of the world that may arise in the future also good at predicting the likelihood of occurrence of specific autobiographical events?).…”
Section: Varieties Of Future Thinkingmentioning
confidence: 99%